Analisi Strategi Pemasaran Rumah Sakit Di Dalam Medical Tourism Di Indonesia - Andreas Agusta (Pemuliaan Keadilan, 2024)
Hospitals as a health facility have become an important part of public health. Facing globalization, hospitals must carry out marketing activities which can be influenced by several factors, including: IT and communications have brought us into a free market era where location and distance are no longer a problem and it is increasingly easy for the public to access information to determine which hospital a patient will seek treatment at. This causes competition between hospitals to become increasingly fierce. To understand the challenges of domestic health services is to improve the quality of services holistically in all aspects of health, including factors assessed by patients such as respect, comfort, order, responsibility and professionalism so that they can match health services abroad. Medical Tourism as part of the Hospital Marketing Strategy in the Tourism Area. The article in this review explains medical tourism and hospital marketing strategies in Indonesia. Hospitals as private businesses use various strategies to attract more patients or customers, such as creating therapy rooms in hybrid hotels (hospitals designed for the comfort of international patients)